Penyuluhan Fisioterapi tentang Kasus Low Back Pain di Posyandu Lansia Kelurahan Kedungkandang - I Made Gandhi Laksana; Nurul Aini Rahmawati; Lisna Lisna (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
The process of aging in the course of human life is a natural thing. A common problem experienced by elderly people related to physical health is that they are susceptible to various diseases, due to reduced body resistance in dealing with external influences. Low back pain or lower back pain is a feeling of discomfort that can cause various kinds of disorders that can cause health problems in human life. So it is important for people to understand about low back pain. Therefore, there is a need to increase knowledge and understanding at community health centers about low back pain, including signs of symptoms, prevention and treatment for the elderly at Posyandu, Kedungkandang Village. The method used is to provide physiotherapy education in the form of health promotion about low back pain to elderly posyandu participants using posters as an educational medium. Questions and answers to participants to measure effectiveness and provide independent training education. The activity ran smoothly and was easily understood by the elderly at the Posyandu, Kedungkandang Village and could increase participants' knowledge about cases of low back pain.